Resource manipulation reveals flexible allocation rules to growth and reproduction in a Mediterranean evergreen oak - Pulido, Fernando; Moreno, Gerardo; Garcia, Eustolia; Obrador, Jose J; Bonal, Raul; Díaz, Mario (JOURNAL OF PLANT ECOLOGY, 2014)
Aims In plants, resource allocation to growth and reproduction may depart from trade-off expectations if (i) investment in growth and reproduction relies on different resource pools, (ii) allocation to reproduction is dependent upon reaching some growth threshold or (iii) reproduction is developmentally linked to growth, both functions relying on the same resource pool. We examined the effects of enhanced resource level on patterns of resource allocation to growth and reproduction in holm oak (Quercus ilex sbsp. ballota), a Mediterranean evergreen tree. Methods In the experimental year (2003), we manipulated the amount of soil nutrients in autumn (to increase nutrient uptake during shoot elongation in the following spring) and soil water in summer (to increase water uptake during acorn growth). Indicators of growth and male and female reproduction were estimated in the pre-experimental (2002), experimental (2003) and post-experimental (2004) years. Important Findings Fertilized trees produced significantly longer shoots, but the number of female flowers per shoot was not affected by treatments. The production of male catkins was also enhanced by fertilization. Irrigation did not affect the production of female flowers or abortion rates. Growth and female reproduction showed no consistent relationship in untreated trees, but resource addition elicited a growth-female reproduction trade-off in the experimental year. The sign of this significant relationship changed in the post-experimental year, indicating the existence of lagged effects of resource manipulation on acorn production. Overall, patterns of allocation to growth and reproduction varied as a function of sex, resource availability and year, a result consistent with extreme allocational plasticity in holm oak.
Keywords: acorn abortion; allocational plasticity; Dehesa; growth-reproduction trade-offs; nutrient addition; Quercus ilex; resource allocation

Establishment limitation of holm oak (Quercus ilex subsp. ballota (Desf.) Samp.) in a Mediterranean savanna — forest ecosystem - Smit, Christian; Díaz, Mario; Jansen, Patrick (Annals of Forest Science, 2009)
• Tree recruitment in Mediterranean savannas is generally hampered, in contrast with the original oak forests where these savannas are derived from. We asked whether this diﬀerence in recruitment success can be explained by diﬀerential post-dispersal survival. For one year we monitored experimentally cached holm oak acorns in a savanna – forest ecosystem in Central Spain, and recorded cache pilferage, type of pilferer, boar rooting, seedling emergence, seedling survival and the cause of mortality. • Cache pilferage was signiﬁcantly lower in savanna (8%) than in forest (21%). However, the higher cache survival was more than oﬀset by lower seedling emergence and, particularly, by nine times higher seedling mortality in savanna, mainly due to desiccation. Wild boar rooting did not diﬀer between experimental caches and controls without acorns, indicating that individual cached acorns do not trigger rooting activity. • Our results indicate that the diﬀerence in post-dispersal survival between savanna and forest is due to lower emergence and, primarily, higher seedling mortality in savanna, not to higher cache pilferage. Absence of safe sites such as shrubs, abundantly present in the forest, may well explain the lack of recruitment in the savanna. Management measures appear necessary for long-term persistence of Mediterranean savannas in general.
Keywords: Dehesa; seed predation; seedling establishment; tree recruitment

Establishment limitation of holm oak (Quercus ilex subsp. ballota (Desf.) Samp.) in a Mediterranean savanna — forest ecosystem - Smit, Christian; Díaz, Mario; Jansen, Patrick (Annals of Forest Science, 2009)
• Tree recruitment in Mediterranean savannas is generally hampered, in contrast with the original oak forests where these savannas are derived from. We asked whether this diﬀerence in recruitment success can be explained by diﬀerential post-dispersal survival. For one year we monitored experimentally cached holm oak acorns in a savanna – forest ecosystem in Central Spain, and recorded cache pilferage, type of pilferer, boar rooting, seedling emergence, seedling survival and the cause of mortality. • Cache pilferage was signiﬁcantly lower in savanna (8%) than in forest (21%). However, the higher cache survival was more than oﬀset by lower seedling emergence and, particularly, by nine times higher seedling mortality in savanna, mainly due to desiccation. Wild boar rooting did not diﬀer between experimental caches and controls without acorns, indicating that individual cached acorns do not trigger rooting activity. • Our results indicate that the diﬀerence in post-dispersal survival between savanna and forest is due to lower emergence and, primarily, higher seedling mortality in savanna, not to higher cache pilferage. Absence of safe sites such as shrubs, abundantly present in the forest, may well explain the lack of recruitment in the savanna. Management measures appear necessary for long-term persistence of Mediterranean savannas in general.
Keywords: Dehesa; seed predation; seedling establishment; tree recruitment

The role of temporal shrub encroachment for the maintenance of Spanish holm oak Quercus ilex dehesas - Ramírez, José Alberto; Díaz, Mario (Forest Ecology and Management, 2008)
Dehesas are man-made systems composed by evergreen oaks (Quercus ilex and Quercus suber) scattered over a grassland understorey. They cover about 3.1 million ha in the southwest of the Iberian Peninsula and are to be preserved under the EU Habitats Directive due to the high levels of plant and animal diversity they maintain. The main current threat to long-term dehesa farming is a chronic absence of natural tree regeneration.We test whether dehesa abandonment would promote natural regeneration, how size structure of tree populations change after abandonment, and whether shrub encroachment would enhance seedling recruitment by measuring the size structure of mature tree populations, shrub cover and seedling density in 17 dehesa farms of known date of abandonment. Size structures were approximately bell-shaped in farms abandoned less than 16 years ago, progressively approaching afterwards the inverse J-shaped distribution typical from holm oak forests. Proportions of young mature trees changed with age of abandonment according to a logistic growth function. Proportions typical from forests (70–80%) were reached 30 years after abandonment, whereas balanced numbers of young and old trees were reached 20–25 years after abandonment. Short-term seedling recruitment was not related to age of abandonment or to covers of most dominant shrubs and was positively related to cover of mature trees and of Cytisus multiflorus, a nurse shrub for holm oak seedlings. Synthesis and applications: Conservation of dehesas and their associated biodiversity values should be based on financing temporal abandonment of productive dehesa farming for 20 years, keeping land in good agricultural condition by re-opening the encroached plots after tree recruitment (i.e. rotational set-aside). The proposed measure has the additional advantages of easy monitoring and straightforward evaluation of its effectiveness.
Keywords: Dehesa; Quercus ilex; Regeneration; rotational set-aside; Shrub cover; Sustainability

The role of temporal shrub encroachment for the maintenance of Spanish holm oak Quercus ilex dehesas - Ramírez, José Alberto; Díaz, Mario (Forest Ecology and Management, 2008)
Dehesas are man-made systems composed by evergreen oaks (Quercus ilex and Quercus suber) scattered over a grassland understorey. They cover about 3.1 million ha in the southwest of the Iberian Peninsula and are to be preserved under the EU Habitats Directive due to the high levels of plant and animal diversity they maintain. The main current threat to long-term dehesa farming is a chronic absence of natural tree regeneration.We test whether dehesa abandonment would promote natural regeneration, how size structure of tree populations change after abandonment, and whether shrub encroachment would enhance seedling recruitment by measuring the size structure of mature tree populations, shrub cover and seedling density in 17 dehesa farms of known date of abandonment. Size structures were approximately bell-shaped in farms abandoned less than 16 years ago, progressively approaching afterwards the inverse J-shaped distribution typical from holm oak forests. Proportions of young mature trees changed with age of abandonment according to a logistic growth function. Proportions typical from forests (70–80%) were reached 30 years after abandonment, whereas balanced numbers of young and old trees were reached 20–25 years after abandonment. Short-term seedling recruitment was not related to age of abandonment or to covers of most dominant shrubs and was positively related to cover of mature trees and of Cytisus multiflorus, a nurse shrub for holm oak seedlings. Synthesis and applications: Conservation of dehesas and their associated biodiversity values should be based on financing temporal abandonment of productive dehesa farming for 20 years, keeping land in good agricultural condition by re-opening the encroached plots after tree recruitment (i.e. rotational set-aside). The proposed measure has the additional advantages of easy monitoring and straightforward evaluation of its effectiveness.
Keywords: Dehesa; Quercus ilex; Regeneration; rotational set-aside; Shrub cover; Sustainability

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P; Pulido, Fernando J (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect

Fruit abortion, developmental selection and developmental stability in Quercus ilex. - Díaz, Mario; Møller, Anders P.; Pulido, Fernando J. (Oecologia, 2003)
Fruit abortion has been hypothesized to be a parental means of selective removal of propagules with low viability. In particular, aborted zygotes have been suggested to have developmentally deviant phenotypes, and surviving offspring may therefore give rise to adults with a developmentally stable phenotype. We tested predictions from this hypothesis using acorns of holm oaks Quercus ilex as a model system. Fecundity of oak trees was negatively related to mean fluctuating asymmetry of leaves, and abortion rates were positively related to leaf fluctuating asymmetry in at least one population. Aborted acorns were asymmetric in 83-99% of cases in three samples, while mature acorns were only asymmetric in 57-78% of cases. Acorn asymmetry was unrelated to germination probability and germination date, and had no significant effect on number of leaves, leaf mass, stem mass, seedling height or leaf area of seedlings. However, acorn asymmetry affected the trade-off between number and size of leaves in seedlings. Seedlings from asymmetric acorns showed a positive relationship between acorn size and number of leaves, but no relationships between acorn size and leaf area, while symmetric acorns showed the opposite. A positive relationship between acorn size and number of leaves in spring was found for naturally emerged seedlings that died during their first summer, whereas the number of leaves produced by surviving seedlings did not depend on acorn size. These findings are consistent with the hypothesis that stressed trees selectively abort propagules of low viability, and that developmental selection acts on a measure of developmental instability of fruits.
The following values have no corresponding Zotero field: accession-num: 12721827
Keywords: acorn; Fluctuating asymmetry; Leaf number; Leaf size; Maternal effect

Food resource matching by foraging tits Parus spp. during spring-summer in a Mediterranean mixed forest; evidence for an ideal free distribution - Díaz, Mario; ILLERA, JUAN CARLOS; ATIENZA, JUAN CARLOS (Ibis, 1998)
We analysed whether patterns of microhabitat use by Blue Tits Parus caeruleus, Great Tits Parus major and Crested Tits Parus cristatus inhabiting a mixed forest consistently matched the patterns of food availability experienced by foraging birds during spring-summer. The use of five microhabitats by each bird species (the foliage of three tree species, shrubs and ground) and the availability of food in trees during the prebreeding, breeding and post-breeding periods of the birds' annual cycle were measured. All three tit species foraged mainly in the outer part of tree canopies (small branches and leaves or needles). Tit distributions between tree species matched food resource distributions irrespective of overall food resource levels, which varied four-fold between the study periods, and tit species. Tits also exploited secondary microhabitats (shrubs and ground) in periods of low food availability; Blue Tits tended to use shrubs, whereas Great and Crested Tits foraged on the ground. Between-trees distributions fitted that expected from an ideal free distribution, suggesting that food availability and intraspecific exploitative competition were the main factors governing tree use by tits. In contrast, patterns of use of secondary microhabitats (shrubs and ground) seemed to indicate a role for the species-specific morphological configurations of each tit species since Blue Tits are better adapted to hang and tended to forage in shubs, whereas Great and Crested Tits are better adapted to feed on horizontal surfaces and tended to forage on the ground. No evidence of interspecific interactions was observed. Overall, the results pointed to an independent exploitation of Mediterranean mixed forest by each bird species, food availability and food accessibility being the main factors affecting microhabitat use by foraging tits.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: food availability; Foraging (voyant); microhabitat use; tits; Tree species

Food resource matching by foraging tits Parus spp. during spring-summer in a Mediterranean mixed forest; evidence for an ideal free distribution - Díaz, Mario; ILLERA, JUAN CARLOS; ATIENZA, JUAN CARLOS (Ibis, 1998)
We analysed whether patterns of microhabitat use by Blue Tits Parus caeruleus, Great Tits Parus major and Crested Tits Parus cristatus inhabiting a mixed forest consistently matched the patterns of food availability experienced by foraging birds during spring-summer. The use of five microhabitats by each bird species (the foliage of three tree species, shrubs and ground) and the availability of food in trees during the prebreeding, breeding and post-breeding periods of the birds' annual cycle were measured. All three tit species foraged mainly in the outer part of tree canopies (small branches and leaves or needles). Tit distributions between tree species matched food resource distributions irrespective of overall food resource levels, which varied four-fold between the study periods, and tit species. Tits also exploited secondary microhabitats (shrubs and ground) in periods of low food availability; Blue Tits tended to use shrubs, whereas Great and Crested Tits foraged on the ground. Between-trees distributions fitted that expected from an ideal free distribution, suggesting that food availability and intraspecific exploitative competition were the main factors governing tree use by tits. In contrast, patterns of use of secondary microhabitats (shrubs and ground) seemed to indicate a role for the species-specific morphological configurations of each tit species since Blue Tits are better adapted to hang and tended to forage in shubs, whereas Great and Crested Tits are better adapted to feed on horizontal surfaces and tended to forage on the ground. No evidence of interspecific interactions was observed. Overall, the results pointed to an independent exploitation of Mediterranean mixed forest by each bird species, food availability and food accessibility being the main factors affecting microhabitat use by foraging tits.
Keywords: food availability; Foraging (voyant); microhabitat use; tits; Tree species